Role of inoculum density and incubation period on saprophytic behaviour of Pythium ultimum and Sclerotium rolfsii - and R.C. TRIPATHI, S. PANDEY, RAM JILAL, S.N. SRIVASTAVA (Indian Phytopathology, 2002)
Field experiments were conducted at Lucknow, Uttar Pradesh, India, to assess the competitive saprophytic ability (CSA) of Pythium ultimum and Sclerotium rolfsii [Corticium rolfsii] isolated from sugarbeets. Boiled wheatsheaf and sugarbeet hypercotylwere buried in soil inoculated with varying densities of inoculum of either species. Results indicated that soil-only baits were not colonized by C. rolfsii, but P. ultimum colonized some pieces of both baits 96 h after burial. It was also found that sugarbeet hypocotyls were a better bait than the wheat straw, and colonization increased (percentage and speed) with inoculum density. In general P. ultimum was the faster and more successful colonizer in these trials.